Use of alcohol in the elderly: transcultural validation of the Michigan Alcoholism Screening Test - Geriatric Version (MAST-G) - Marcia Yumi Kano; Manoel Antônio dos Santos; Sandra Cristina Pillon (SciELO, 2014)
Objective: To evaluate the internal consistency of the version of the Michigan Alcoholism Screening Test - Geriatric Version (MAST-G) instrument, translated and adapted for Brazil. Method: This was a descriptive, cross-sectional study. Data were collected through a demographic questionnaire, the ICD-10 and the MAST-G, following the steps of translation and cultural adaptation. One hundred eleven elderly in the city of São Carlos, SP, Brazil were interviewed. Results: The mean age of those interviewed was 70 years, with 45% men and 55% women, with the mean education of three years; 92% resided with family; 48% of the subjects consumed alcoholic beverages. The MAST-G presented a good level of reliability, with Cronbach's α = 0.7873, and good levels of sensitivity and specificity with a cutoff score of five positive responses. Conclusion: The Brazilian version of the MAST-G presented internal consistency values similar to the original English version,showing it to be adequate for use in the national context.